2021
DOI: 10.1002/ijgo.13562
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass tag‐based quantitative proteomic profiling of the serum of patients with abnormal uterine bleeding associated with copper intrauterine device

Abstract: Objective To investigate changes in the level of protein in serum and uncover the underlying pathogenesis of abnormal uterine bleeding (AUB) associated with copper intrauterine devices (Cu IUD). Methods Protein profiles were investigated via tandem mass tag (TMT)‐based quantitative proteomics and bioinformatics technology. Quantification and characterization of candidate proteins were further performed in 33 controls and 45 cases by Luminex assay and enzyme‐linked immunosorbent assay. Results In total, 842 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the last few years, quantitative proteomics based on tandem mass tagging (TMT) has been widely used for proteomic analysis due to its high throughput, high sensitivity and excellent accuracy [15,16]. For example, Liu et al [17] used tandem mass tag (TMT)-based quantitative proteomics to analyze the changes in protein levels in the serum of patients with abnormal uterine bleeding associated with copper IUDs. The results showed that 25 differentially expressed proteins were observed (P < 0.05), including 8 up-regulated and 17 down-regulated proteins, with signi cantly higher expression of α-1-antitrypsin (a1AT) in women with Cu IUD-associated AUB compared to healthy controls.…”
mentioning
confidence: 99%
“…In the last few years, quantitative proteomics based on tandem mass tagging (TMT) has been widely used for proteomic analysis due to its high throughput, high sensitivity and excellent accuracy [15,16]. For example, Liu et al [17] used tandem mass tag (TMT)-based quantitative proteomics to analyze the changes in protein levels in the serum of patients with abnormal uterine bleeding associated with copper IUDs. The results showed that 25 differentially expressed proteins were observed (P < 0.05), including 8 up-regulated and 17 down-regulated proteins, with signi cantly higher expression of α-1-antitrypsin (a1AT) in women with Cu IUD-associated AUB compared to healthy controls.…”
mentioning
confidence: 99%